Efek Induksi Mutasi Radiasi Gamma Terhadap Pertumbuhan Fisiologis Tanaman Kedelai (Glycine Max (L) Merrill) - Ateng Supriyatna; Aida Syakira Khoerunnisa; Alika Maulidina; Ilvi Maulidina; Indrianita D M Nur Azizah (Lembaga Pengembangan Kinerja Dosen, 2023)
Literature studies can examine the effect of gamma radiation on physiological aspects of soybean plants. Gamma radiation is known to impact genetic diversity, growth, morphology, seed size, weight and protein content of soybean plants. The aim of this literature study is to examine the effects of providing gamma rays on the physiology of soybean plants (Glycine max (L) Merrill). The method used is literature or literature study where the author uses several pieces of literature as references in the journal he created. Some studies show that gamma radiation can cause a decrease in the ability of soybean plants to survive and can cause slower growth. However, other research also shows that gamma radiation can be used to induce genetic mutations that have an impact on the physiology of soybean plants. The discussion topics taken range from the process of gamma radiation inducing genetic mutations in soybean plants, analysis of mutations that occur in soybean growth, the effect of gamma ray radiation on plant growth, and the effect of gamma radiation mutations on physiological parameters: photosynthesis of soybean plants.